2018
DOI: 10.1016/j.cllc.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab in Japanese Patients With Previously Treated Advanced Non–Small-Cell Lung Cancer: A Subgroup Analysis of the Phase 3 OAK Study

Abstract: Atezolizumab was effective and well tolerated in pretreated Japanese patients with NSCLC. Results are consistent with the primary analysis of OAK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
92
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(100 citation statements)
references
References 24 publications
6
92
1
1
Order By: Relevance
“…However, most participants in clinical trials of immune‐checkpoint inhibitors have come from western countries, with Asian/East Asian patients accounting for only 3%–25.2% of the study populations in clinical trials of PD‐1/PD‐L1 inhibitors for NSCLC . Few studies have thus reported on the efficacy of immunotherapy and the related characteristics in Asian patients …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, most participants in clinical trials of immune‐checkpoint inhibitors have come from western countries, with Asian/East Asian patients accounting for only 3%–25.2% of the study populations in clinical trials of PD‐1/PD‐L1 inhibitors for NSCLC . Few studies have thus reported on the efficacy of immunotherapy and the related characteristics in Asian patients …”
Section: Introductionmentioning
confidence: 99%
“…0.52 [0.38–0.72]), though pembrolizumab showed similar pharmacokinetic characteristics in Asians and Caucasians . Two Phase II studies of later‐line nivolumab and a subgroup analysis of atezolizumab in Japanese patients all demonstrated a greater objective response rate (ORR), progression‐free survival (PFS) and overall survival (OS) compared to the overall population . Nivolumab resulted in a median OS of 16.3–17.1 months in Japanese patients with advanced or recurrent squamous or nonsquamous NSCLC, with ORRs of 25.7 and 22.4%, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations